Heritage building conservation : an overview of Pahang State Museum - Muhamad Amirul Hafiz Zulkifli; Mohd Syuhaidi Abu Bakar; Mohamad Syafiq Mat Shuki (Penerbit Universiti Kebangsaan Malaysia, 2020)
This research identified the condition of the Pahang State Museum in Pekan, Pahang based on the Heritage Building's Conservation Guidelines issued by the National Heritage of Malaysia (2012). The qualitative method is applied through coding and field research to investigate the compliance of the Conservation Guidelines towards the preservation of the museum itself. The objective of this research is not to evaluate the management of the museum but to observe approaches towards its conservation. The study found that the original state of the Pahang State Museum was still in its original form. At the same time, Pahang State Museum management applied the Heritage Building Conservation Guidelines (2012) directly by implementing the conceptualized as a museum in a garden, and appropriately named ‘The Intelektual Garden’. This research has not only answered the objectives and questions of the study but has also revealed one thousand stories about the building of the Pahang State Museum whether visually or historically. This study should inspire better preservation and maintenance of buildings.